Understanding the Resurgence of Traditional Authorities in Post-Apartheid South Africa - Ainslie, Andrew; Kepe, Thembela (Journal of southern African studies, 2016)
Drawing their power not from the ballot box but from a supposedly ancient wellspring of power, hereditary traditional authorities in postcolonial Africa have frequently posed challenges for incoming 'democratic' governments. The situation in post-apartheid South Africa is no different. However contentious their role under the colonial and apartheid systems of government was, the Constitution of the new South Africa (1996) recognised traditional authorities and afforded them opportunities for a political resurgence. This article reviews the changing status of traditional authorities in the Eastern Cape province over the 20 years since 1994. It explores the resurgence of the chiefs in relation to the consolidation of democratic processes and of emergent, neo-patrimonial modes of government. It briefly considers the role of traditional authorities in three key and closely related spheres, namely the institution of the Eastern Cape House of Traditional Leaders, the question of how gender is handled by and within traditional institutions, and the continuing challenges of land administration and development in rural areas. In all these spheres, and in the face of real opposition, the voice and influence of traditional authorities have emerged stronger than ever. We conclude by suggesting that, as they are drawn deeper into governance and have to play a formal role in addressing the myriad institutional challenges, new questions will and should be asked about the status and influence of traditional authorities, and their substantive contribution to democracy in South Africa.